Proposal of a quality management design based on the ISO 17025- 2005 standard in the clinical laboratory of the "Enrique Ponce Luque" Health Center belonging to the health district 12d01 of the city of Babahoyo - Los Ríos - Ecuador - Casco López, María Gabriela; Junco Vaca, Agustín Ignacio; Sterling Varas, Erick Xavier (Ingeniería Química y Desarrollo, 2024)
The authors conducted a clinical laboratory diagnosis through observation, followed functioning of the laboratory on separate days to assess specific aspects included in a checklist based on ISO  17025-2005, plus its own analysis interviews were conducted to all workers to collect data from their perspective and obtain verifiable data, this information was subsequently processed and analyzed in a cause-and-effect diagram ISHIKAWA. Results:  80% of the requirements from the checklist are not meted, partially implemented requirements were 14.29 % and finally 5.71% implemented requirements are met. Conclusions: Overall compliance was low; this allows us to conclude that in terms of calibration and traceability clinical laboratory Enrique Ponce Laquez does not have the minimum requirements for operation in accordance with international standards.
Keywords: Agency; Law; quality; laboratory